Dampak Serangan Israel terhadap Kualitas Lingkungan, Air, dan Tanah di Palestina - Latif, Annisya Nurul; Muttaqin, Muhammad Izdiyan; Firmansyah, Indra Arif (Indonesia Center for Middle East Studies, 2025)
Environmental pollution in areas of armed conflict has become a global issue that has a direct impact on ecosystem sustainability and human welfare. In the context of Palestine, the protracted conflict and Israeli occupation are associated with the degradation of environmental quality, particularly in soil and groundwater. This study examines the impact of armed conflict on environmental degradation and public health in Palestine by placing it within the geopolitical framework of the Israeli–Palestinian conflict. This research uses a qualitative approach based on literature studies and secondary data from international organization reports, scientific publications, and international legal documents. The results of the study showed that damage to water and sanitation infrastructure, military activities, and explosives and weapons residues including indications of the use of white phosphorus contributed to increased soil chemical contamination and decreased groundwater quality. This condition correlates with increased public health risks, especially in vulnerable groups such as children, and exacerbates socio-economic crises and food security. These findings affirm the urgency of integrating environmental restoration into the humanitarian agenda and post-conflict reconstruction, as well as the importance of strengthening environmental protection and accountability mechanisms within the framework of international law.